Tick (Acari: Ixodidae) infestation in cattle from Sleman, Yogyakarta Province, Indonesia - ANA SAHARA; BAMBANG HERU BUDIANTO; RONY MARSYAL KUNDA; LINTANG WINANTYA FIRDAUSY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sahara A, Budianto BH, Kunda RM, Firdausy LW. 2023. Tick (Acari: Ixodidae) infestation in cattle from Sleman, Yogyakarta Province, Indonesia. Biodiversitas 24: 4087-4094. Massive attacks of were found Haemaphysalis bispinosa in beef cattle farms in Sleman Regency, Yogyakarta, Indonesia. Besides it makes blood loss, they also have the potential to become vectors of several diseases. The aim of this research is to evaluate the prevalence of infestation, describe the morphology, fecundity, and timing of oviposition, as well as the preferred attachment sites for ticks. The samples were collected manually, and the body of the cattle was divided into four regions to determine the preferred sites of attachment of ticks. The morphology and occurrence of tick attachment sites, egg production, and hatchability were examined macroscopically and microscopically, and the obtained data we assessed descriptively and qualitatively. The findings indicated that, in contrast to the body area and the front and back legs, the tick predilection locations were the head, ears, and neck region. An engorged female may generate an average of 731.5±106 eggs throughout her 10-day oviposition cycle. After 17-30 days, tick eggs hatch into larvae; on average, 626.3±56 eggs per tick female successfully hatch into larvae.